A Critical Discourse Analysis of Hillary Clinton's Presidential Campaign (2016) - MOULAY, Houda (My University, 2017)
This research work aims at extracting the discursive structures in Hillary Clinton's presidential election campaign discourse of 2016. Using Fairclough's framework of critical discourse analysis, the work attempts to uncover the elements of gender references, rhetoric, frames and intertextuality in the Campaign Launch speech and the Concession Speech. The study is divided into three chapters. The first one introduces the theory of Critical Discourse Analysis. In addition, it highlights the notions of rhetoric, the political discourse and the U.S. presidential campaign. The second chapter introduces Hillary Clinton and explains the methods and describes the data. It, further, sheds light on the framework of analysis. The third chapter is devoted to the critical discourse analysis of Clinton's Launch and Concession Speeches of the election campaign. The analysis starts at the level of the text and moves to discursive practice level. At last, we came up to identifying the elements of gender references, frames, intertextuality and rhetorical techniques that are underlying in both speeches.
The Launch & Concession Speeches (Fairclough's Framework)
Keywords: CDA (Critical Discourse Analysis); Fairclough's Framework; Hillary Clinton; U.S. Presidential Election 2016; Rhetoric; Framing; Intertextuality; Gendered discourse